Predicting election popularity of a person using crowd sensing in social networks - Nadi, Mashroora; Ahmad, Syed Washfi; Rahman, S.M.Saquib (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.